Psychological teleconsultations in patients suffering from chronic skin diseases during the COVID-19 era: a service to improve patients' quality of life. (3rd April 2022) - Marasca, Claudio; De Rosa, Anna; Fabbrocini, Gabriella; Cantelli, Mariateresa; Patrì, Angela; Vastarella, Maria; Gallo, Lucia; di Vico, Francesca; Poggi, Serena; Ruggiero, Angelo
Abstract: The COVID-19 era represented an important stressful event affecting population in many different ways, with important negative impact on social, working and relational life. Indeed, the home-isolation in addition to the high-level of distress given by fear of infection, has significantly resulted in a large number of psychological-consequences. Moreover, in order to guarantee a continuity of care, different measures have been applied among hospitals such as the implementation of teledermatology services. For these reasons, we implemented at our Dermatological-Clinic psychological video-consultations through our teledermatology-services. Herein we report our experience of 23 psychological-video-consultations, which led to achieve a significant reduction of DLQI (from 4.4 ± 3.9 at baseline to 1.6 ± 2.5 at week-4) in patients suffering from chronic skin conditions during the COVID-19 era.